Wearable Patch for Mass Casualty Screening with Graphene Sensors - Vićentić, Teodora; Rašljić Rafajilović, Milena; Ilić, Stefan; Koteska, Bojana; Madevska Bogdanova, Ana; Pašti, Igor; Lehocki, Fedor; Spasenović, Marko (My University, 2022)
Wearable sensors are reaching maturity, at the same time as technologies for communicating physiological data and those for analyzing massive amounts of data. The combination of the three technologies invites for applications in mass screening of personal health through smart algorithm deployment on data from wearable patches. We propose and present an architecture for a wearable patch to be used in mass casualty emergency situations, or for hospital bedside monitoring. The proposed patch will contain multiple sensors of physiological parameters. We propose to create respiration and heartbeat sensors made of laser induced graphene. We show that graphene on flexible substrates can be utilized in conjunction with the Python heart rate analysis toolkit - HeartPy to reliably acquire physiological data from human subjects.
Keywords: wearables, graphene, Python, sensors, electronics